PSYCHOLOGICAL ASSISTANCE MODEL FOR PATIENTS AT MUHAMMADIYAH PONOROGO HOSPITAL - Nur Amalina, Afifah Ismahani; Aisya, Riska Nur; Anggita, Evi Dina; Erwahyudin, Devid Dwi (TARBAWI:Journal on Islamic Education, 2024)
Basically, an individual's Physical and Mental Health will be interrelated with each other.Patientswhoarediagnosed withchronicillnessesandrequirehospitalizationareathigh riskof experiencingdepression,stressandanxiety whichof course canhaveanimpactonthe physical health recovery process. If we look at this phenomenon, psychological assistance is really needed to support the patient's physical healing. This research aims to examine what psychological assistance services are and also how effective the psychological assistance services at the Muhammadiyah Ponorogo Hospital are as one of the health services in PonorogoCity. Thisresearch wasconductedusingqualitativemethods, withdirectedinterview techniques and library studies. The results obtained from the research are; (1) The Muhammadiyah Ponorogo Hospital providespsychological assistance servicesin the form ofspiritual guidance. (2) The Spiritual Guidance Model at the Muhammadiyah Ponorogo General Hospital is in the form of; (a) Personal assistance, (b) through the media and (c) Group assistance. (3) The effectiveness of the mentoring model is influenced by two factors, namely the form of mentoring method and effective communication